Is there a role for sarcolipin in avian facultative thermogenesis in extreme cold?. (24th June 2020) - Stager, Maria; Cheviron, Zachary A.
Abstract : Endotherms defend their body temperature in the cold by employing shivering (ST) and/or non-shivering thermogenesis (NST). Although NST is well documented in mammals, its importance to avian heat generation is unclear. Recent work points to a prominent role for the sarco/endoplasmic reticulum Ca 2+ ATPase (SERCA) in muscular NST. SERCA's involvement in both ST and NST, however, posits a tradeoff between these two heat-generating mechanisms. To explore this tradeoff, we assayed pectoralis gene expression of adult songbirds exposed to chronic temperature acclimations. Counter to mammal models, we found that cold-acclimated birds downregulated the expression of sarcolipin ( SLN ), a gene coding for a peptide that promotes heat generation by uncoupling SERCA Ca 2+ transport from ATP hydrolysis, indicating a reduced potential for muscular NST. We also found differential expression of many genes involved in Ca 2+ cycling and muscle contraction and propose that decreased SLN could promote increased pectoralis contractility for ST. Moreover, SLN transcript abundance negatively correlated with peak oxygen consumption under cold exposure (a proxy for ST) across individuals, and higher SLN transcript abundance escalated an individual's risk of hypothermia in acute cold. Our results therefore suggest that SLN-mediated NST may not be an important mechanism of—and could be a hindrance to—avian thermoregulation in extreme cold.